Functional assessment of all polyethylene tibial monoblock component in total knee arthroplasty - Moinuddin Nadaf; Sharan S Patil; Raghavendra R Huchchannavar (Journal of Applied Pharmaceutical Research, 2023)
Background: In a developing country like India the cost effectiveness of all polyethylene tibial components is a major boon, without compromising the functional outcome. In this study we have attempted to evaluate the functional outcome of all polyethylene tibial monoblock component in total knee arthroplasty. Methodology: The study was carried out on 86 patients who are operated for total knee arthroplasty with all polyethylene tibial monoblock component. Demographic, surgical and follow up data was collected from case sheets of patients and copied in Performa. The patients were called for five years follow up and examined in the outpatient department. Results: The mean age of study population was 62.8 years (range 50 – 72 years) with mean BMI of 27.6 kg/m2. Statistically significant improvement was seen in the range of movements in all the age groups. Both male and female patients had insignificant difference in knee scoring. Assessment of clinical functional abilities of knee scoring have observed to be higher in patients with lower BMI. Conclusion: Significant improvement in range of motion as well as knee score in all age range, emphasizes the fact that total knee arthroplasty with all polyethylene design in osteoarthritis is an excellent surgery to restore near normal life style.